Human Type 1 Diabetes Is Characterized by an Early, Marked, Sustained, and Islet-Selective Loss of Sympathetic Nerves - Mundinger, Thomas O.; Mei, Qi; Foulis, Alan K.; Fligner, Corinne L.; Hull, Rebecca L.; Taborsky, Gerald J. (Diabetes (New York, N.Y.), 2016)
In humans, the glucagon response to moderate-to-marked insulin-induced hypoglycemia (IIH) is largely mediated by the autonomic nervous system. Because this glucagon response is impaired early in type 1 diabetes, we sought to determine if these patients, like animal models of autoimmune diabetes, have an early and severe loss of islet sympathetic nerves. We also tested whether this nerve loss is a permanent feature of type 1 diabetes, is islet-selective, and is not seen in type 2 diabetes. To do so, we quantified pancreatic islet and exocrine sympathetic nerve fiber area from autopsy samples of patients with type 1 or 2 diabetes and control subjects without diabetes. Our central finding is that patients with either very recent onset (<2 weeks) or long duration (>10 years) of type 1 diabetes have a severe loss of islet sympathetic nerves (Δ = −88% and Δ = −79%, respectively). In contrast, patients with type 2 diabetes lose no islet sympathetic nerves. There is no loss of exocrine sympathetic nerves in either type 1 or type 2 diabetes. We conclude that patients with type 1, but not type 2, diabetes have an early, marked, sustained, and islet-selective loss of sympathetic nerves, one that may impair their glucagon response to IIH.